Integrating minorities in the classroom - Gendre, Alexandra de,Karbownik, Krzysztof,Salamanca, Nicolás,Zenou, Yves (CESifo, 2024)
We develop a multi-agent model of the education production function where investments of students, parents, and teachers are linked to the presence of minorities in the classroom. We then test the key implications of this model using rich survey data and a mandate to randomly assign students to classrooms. Consistent with our model, we show that exposure to minority peers decreases student effort, parental investments, and teacher engagement and it results in lower student test scores. Observables correlated with minority status explain less than a third of the reduced-form test score effect while over a third can be descriptively attributed to endogenous responses of the agents.
10419/300033
Keywords: Graue Literatur; minorities; indigenous students; peer effects; student effort; parental investments; teachers